Sonographische und sedimentologische Untersuchungen in der Laptevsee, sibirische Arktis (Teil 2, Laborarbeit) - Lindemann, Frank (1994)
During summer 1993 the expedition TRANSDRIFT I with the russian R/V 'Ivan Kireyev' was carried out in the Laptev Sea (Northern Siberia, Arctic Ocean). Aims of the expedition included the detection of accumulation areas of sediment discharge and to get some ideas of the interaction of ice and seafloor in this shallow shelf region. To characterise the modern siliciclastic surface sediments in the Laptev Sea and to map the accumulation areas of the sediment discharge, detailed granulometric studies were carried out on 48 surface samples. At the same time, side-scan profiles were analysed to get ideas of drift pattem and distribution of grounded ice. The sediment distribution pattems show that the westem Laptev Sea is dominated by relict delta sands. Accumulation areas of the sediment discharge, which was contribute to the western Laptev Sea by rivers seem to be restricted to valleys formed during Pleistocene time. In the eastern Laptev Sea and especially in the south-east, surface sediments are dominated by silt and clay. These fine-grained sediments trace the modern deposition areas of sediment discharge of the great river systems Lena and Yana in the eastem Laptev Sea. In some shelf samples, a depression (ca. 1 Phi wide) in the grain size distribution within the silt fraction around 6 Phi, may give a first hint of ice formation processes in some regions of the Laptev Sea. Analyses of side scan sonar records show no dominant direction of ice gouges in the Laptev Sea, indication a rather random drift direction. However, over wide spread areas in the Laptev Sea ice gouging is a significant geological agent influencing the sediment pattem by resuspension and bulldozing.